Rancang Bangun Prototype Alat Peraga Pengoperasian Palka dengan Rain Sensor - Samudra, Edwin; Narto, Amad; Sapan, Yustina; Utari, Riyadini (Majalah Ilmiah Gema Maritim, 2023)
Rain sensor is a sensor that functions as a rainwater detection device, this sensor if exposed to rainwater on the sensor board then the resistance will change. The application of this sensor can be used on the hatch cover on ships automatically so that when it rains the sensor detects and will give a warning or for additional use can be used for the operation of closing the hatch, for the types on the market there are FC37 and YL83. This research uses Research and Development methods, starting from analysis, design, design, programming, and testing. In this study, the operating model of hatch props using rain sensors was determined, namely by using a circuit, Arduino Uno as a microcontroller, and several types of sensors as supporting devices. The result of making this prop is to facilitate learning for cadets and this prop is also a miniature on board, so the author hopes that this prop can be developed again for future research, and with the use of this rain sensor will help the ship's crew in operating the hatch automatically.